Capability Level Assessment of IT Governance in the SIAP KOJA Application Using the COBIT 2019 Framework - Widasari, Yesya Najwa; Oktadini, Nabila Rizky (Journal of Applied Informatics and Computing, 2025)
This study assesses the IT governance capability of the SIAP KOJA application at the Jambi City Department of Communication and Informatics (Diskominfo). SIAP KOJA was introduced to strengthen attendance discipline, transparency, and accountability through geofencing and biometric features. Using the COBIT 2019 framework, the assessment aligns IT processes with institutional objectives and focuses on two key processes: APO11 (Manage Quality) and BAI05 (Manage Organizational Change Enablement). Data were collected through a literature review, interviews, observations, and a structured questionnaire based on the COBIT 2019 Process Assessment Model. The sample comprised five personnel from Diskominfo’s Informatics Applications Division, purposively selected for their direct involvement in planning, development, and operations. Results indicate Level 3 (Defined) capability for both APO11 and BAI05 with standards documented. At Level 4, APO11 reached 75.56% (Largely Achieved) and BAI05 reached 76.00% (Largely Achieved). Because these fall below the ≥85% “Fully Achieved” threshold, progression was halted, and the capability level remains Level 3. Limitations in structured measurement and continuous monitoring contribute to a two-level gap from the Level 5 (Optimizing) target. The study recommends formalizing a quality management system with service-level agreements and performance indicators; strengthening outcome-based change management through compliance audits and systematic user feedback; and institutionalizing lessons learned. These improvements are essential for enhancing governance capability, ensuring system reliability, and supporting successful digital transformation in local government.